Cumulative digital risk exposure and self-harm behavior among Indonesian adolescents - Triyana Harlia Putri; Fitri Ariyanti Abidin; Meita Dhamayanti; Popy; Fitri Fujiana; Aprida Manurung; Suryani Suryani (BMC Public Health, 2026)
Abstract Background Self-harm behavior (SHB) among adolescents is a growing public health concern, particularly in the digital era. Exposure to digital risks such as online gaming addiction and cyberbullying victimization may increase vulnerability, especially when multiple risks co-occur. This study examined the association between cumulative digital risk exposure and SHB among Indonesian adolescents and identified associated psychosocial factors. Methods A cross-sectional study was conducted among 1,742 Indonesian adolescents recruited using a multistage school-based sampling approach. Data were collected using structured questionnaires assessing sociodemographic characteristics, online gaming addiction, cyberbullying victimization, and SHB. Instruments included the Indonesian Online Game Addiction Questionnaire, the Cyberbullying and Online Aggression Survey Instrument, and the Self-Harm Inventory. Bivariate analyses and multivariable binary logistic regression were performed. Results Overall, 33.1% of participants met the criteria for online gaming addiction, 57.5% reported cyberbullying victimization, and 55.0% reported SHB. Based on the cumulative digital risk index, 38.9% of participants had no digital risk, 31.7% had one digital risk, and 29.4% had two digital risks. SHB prevalence differed across digital risk groups (43.3%, 67.8%, and 56.7%, respectively). In multivariable analysis, one digital risk was associated with higher odds of SHB compared with no digital risk (AOR = 2.20, 95% CI: 1.71–2.82), whereas the association for two digital risks was attenuated after adjustment (AOR = 0.56, 95% CI: 0.40–0.78). No significant linear dose–response relationship was observed (p for trend = 0.411). A history of violence (AOR = 4.19, 95% CI: 2.50–7.02), low academic performance, lower parental income, having fewer than three close friends, and parental separation/divorce were independently associated with higher odds of SHB, whereas female sex was associated with lower odds (AOR = 0.57, 95% CI: 0.46–0.72). Conclusion Cumulative digital risk exposure was associated with SHB among Indonesian adolescents; however, the association did not demonstrate a linear dose–response pattern after adjustment for psychosocial factors. A history of violence emerged as the strongest correlate of SHB, highlighting the importance of addressing both digital and broader psychosocial vulnerabilities in adolescent self-harm prevention.